High resolution adaptive optics imaging complements standard spectral domain optical coherent tomography in retinal diseases with micro-structural details: a case series - Gibran Syed Khurshid; Sasha Strul; Adam Boretsky; Massoud Motamedi; Praveena Gupta (Vision Pan-America, 2015)
Purpose: To evaluate if high resolution adaptive optics confocal scanning laser ophthalmoscopy (AO-SLO) can be used as an adjunct complementary diagnostic tool to spectral domain optical coherent tomography (SD-OCT) in characterizing three macular diseases: rod-cone dystrophy, acute retinal pigment epitheliitis (Krill’s disease), and occult macular dystrophy.